2009
DOI: 10.1007/s10654-009-9399-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal overweight and smoking: prenatal risk factors for caries development in offspring during the teenage period

Abstract: This study aimed to investigate pre- and perinatal determinants as risk factors for caries development in offspring. In this longitudinal register-based cohort study, we included all children (n = 18,142), of 13 years of age who resided in the county of Stockholm, Sweden, in 2000. The cohort was followed until individuals were 19 years of age. In total, 15,538 subjects were examined. Dental caries (decayed, missing and filled teeth/surfaces), were collected from the Public Health Care Administration in Stockho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 49 publications
1
41
1
1
Order By: Relevance
“…Currently, reports [25,26] show that prematurely born individuals have poor mineralization of the teeth and poorer oral health indicators, supporting the evidence of the role played by enamel defects in the development of ECC. Moreover, in a 7-year cohort study, Targino et al (2011) [24] revealed that enamel defects constitute a risk factor for the development of early childhood caries.…”
Section: Discussionmentioning
confidence: 74%
“…Currently, reports [25,26] show that prematurely born individuals have poor mineralization of the teeth and poorer oral health indicators, supporting the evidence of the role played by enamel defects in the development of ECC. Moreover, in a 7-year cohort study, Targino et al (2011) [24] revealed that enamel defects constitute a risk factor for the development of early childhood caries.…”
Section: Discussionmentioning
confidence: 74%
“…Fourteen studies used a case-control format [13–24,26,27], and one study used a cohort format [25] (Table 1). Nine studies focused on SHS [1416,18,20,21,23,24,26].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies focused on SHS [1416,18,20,21,23,24,26]. Another study focused on social variables including SHS [13,22], low birth weight [17], breastfeeding [19], and associated factors [25,27]. Studies were conducted in the United States (US) [1517,19,27], Japan [18,21,22,24,26], eight European countries [13], the United Kingdom (UK) [14], South Africa [20], Belgium [23], and Sweden [25].…”
Section: Resultsmentioning
confidence: 99%
“…Lifestyle factors and dietary habits are also investigated by questionnaire. Relevant EJE references can be found in [35][36][37][38][39][40][41][42][43][44][45].…”
Section: Methodsmentioning
confidence: 99%